Educators by proxy: Emergency remote teaching and learning in the voice of parents - Seabra, Filipa; Abelha, Marta; Aires, Luísa; Teixeira, António Moreira (Frontiers in Education, 2023)
The Covid-19 pandemic led educational systems worldwide to transpose activities planned for face-to-face education to mediated contexts - through what is known as Emergency Remote Teaching and Learning (ERTL). This posed unprecedented challenges to schools, teachers, families, and students. In this context, it was relevant to describe and understand how parents perceived this process, including what challenges to themselves and their children they faced and what advantages they acknowledged in the process. The present study focuses on Portuguese parents’ views on this process. Data were gathered in April and May 2020 through an online questionnaire answered by 184 parents of preschool, basic, and secondary education students (ages 3–18). The present paper presents data from open questions analyzed by deductive and inductive content analysis using MaxQDA. Results evidence three overarching themes: equity, parental labor, and the meaning of school. Parents reveal substantial difficulties juggling the role of proxy educator and parent and point to inequalities - including those concerning very young children, children with disabilities or learning difficulties, students enrolled in professional education, families with insufficient access to technologies, and parents working from home. The school is portrayed as a crucial environment for development, a designated space for learning and caretaking, but also a relational and emotional context. Despite this scenario, parents acknowledge ERTL as having positive aspects and as the possible outlet to keep education going even in extreme situations.